2017
DOI: 10.1080/13697137.2017.1282452
|View full text |Cite
|
Sign up to set email alerts
|

Age-related prevalence of osteoporosis and fragility fractures: real-world data from an Austrian Menopause and Osteoporosis Clinic

Abstract: Objectives: Age and bone mineral density (BMD) are the most relevant determinants for public health authorities to govern the management of osteoporosis. The objectives of this study were to determine the age-related prevalence of osteopenia and osteoporosis according to WHO criteria and fragility fractures in middle-aged and older women. Methods: Women 40 years, who were referred to a menopause and osteoporosis outpatient clinic for BMD measurements, were assessed for patient characteristics, BMD and previous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
36
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(42 citation statements)
references
References 21 publications
6
36
0
Order By: Relevance
“…This is in accordance with the gender trend of fractures, in which men younger than 50 years have a higher incidence of fractures, but after the age of 50 years, the incidence increases markedly in women and decreases in men [2, 6]. Older female patients often are at high risk of osteoporosis [22, 23]. Decreased bone quality leads to more low-energy traumatic fractures, and this study demonstrated a higher incidence of Schatzker type I, II, and III fractures and one-column fractures in elderly patients than that reported in the literature for younger patients [3, 15].…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…This is in accordance with the gender trend of fractures, in which men younger than 50 years have a higher incidence of fractures, but after the age of 50 years, the incidence increases markedly in women and decreases in men [2, 6]. Older female patients often are at high risk of osteoporosis [22, 23]. Decreased bone quality leads to more low-energy traumatic fractures, and this study demonstrated a higher incidence of Schatzker type I, II, and III fractures and one-column fractures in elderly patients than that reported in the literature for younger patients [3, 15].…”
Section: Discussionsupporting
confidence: 73%
“…Decreased bone quality leads to more low-energy traumatic fractures, and this study demonstrated a higher incidence of Schatzker type I, II, and III fractures and one-column fractures in elderly patients than that reported in the literature for younger patients [3, 15]. It is well known that osteoporotic fractures are a frequent and important cause of disability and rising medical costs worldwide; however, researchers on osteoporotic or senile fractures have usually concentrated on the classic fragility fractures of the proximal humerus, distal radius, and proximal femur [23, 24]. Although only 7.34% (24/327) of fractures in this study were due to falling on the ground and can be accurately categorized as fragile fractures, it is obvious that the influence of age or estrogen-related bone structural changes in this group of patients cannot be ignored.…”
Section: Discussionmentioning
confidence: 81%
“…In pre-menopausal Dutch women, the prevalence of osteopenia was 27.3%, and 4.1% of the women were osteoporotic; and in Canadian women, the prevalence of osteoporosis was 20%. 15 Compared to the Western World, the prevalence of osteopenia and osteoporosis is much higher in our and other Indian studies, reflecting poor overall health of menopausal women and women in general in India. 6,8 The prevalence of low BMD (osteopenia and osteoporosis) is 77% in our study (50.5% with osteopenia and 26.5% with osteoporosis).…”
mentioning
confidence: 54%
“…Menopause is an important life transition that all women go through, and it accompanies many significant physical and psychological changes, such as bone loss (Boschitsch, Durchschlag, & Dimai, ), obesity (Goncalves, Silveira, Campos, & Costa, ), depression, and anxiety (Bromberger & Epperson, ; Gracia & Freeman, ). The reason why menopausal women undergo such changes is directly related to the low level of endogenous estrogens.…”
Section: Introductionmentioning
confidence: 99%